A History of Western Society from antiquity to the enlightenment : volume 1 - Wiesner, Merry E. 1952-; Crowston, Clare Haru 1968-; Perry, Joe; MacKay, John P. 1938- (Boston New York Bedford/Saint Martin's, 2022)
A lively journey through the story of Western civilization, focusing on societies, cultures, and the lives of both ordinary and extraordinary men and women.
Keywords: Schulbuch